Acute physical exercise improves shifting in adolescents at school: evidence for a dopaminergic contribution - Berse, Timo; Rolfes, Kathrin; Barenberg, Jonathan; Dutke, Stephan; Kuhlenbäumer, Gregor; Völker, Klaus; Winter, Bernward; Wittig, Michael; Knecht, Stefan (Frontiers in Behavioral Neuroscience, 2015)
The executive function of shifting between mental sets demands cognitive flexibility. Based on evidence that physical exercise fostered cognition, we tested whether acute physical exercise can improve shifting in an unselected sample of adolescents. Genetic polymorphisms were analyzed to gain more insight into possibly contributing neurophysiological processes. We examined 297 students aged between 13 and 17 years in their schools. Physical exercise was manipulated by an intense incremental exercise condition using bicycle ergometers and a control condition which involved watching an infotainment cartoon while sitting calm. The order of conditions was counterbalanced between participants. Shifting was assessed by a switching task after both conditions. Acute intense physical exercise significantly improved shifting as indicated by reduced switch costs. Exercise-induced performance gains in switch costs were predicted by a single nucleotide polymorphism targeting the Dopamine Transporter (DAT1/SLCA6A3) gene suggesting that the brain dopamine system contributed to the effect. The results demonstrate the potential of acute physical exercise to improve cognitive flexibility in adolescents. The field conditions of the present approach suggest applications in schools.